COGNITIVE DEVELOPMENT OF STUDENTS IN FOREIGN LANGUAGE ACQUISITION - Natalia Saienko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The article highlights the necessity and possibility of students' psychological and cognitive development by means of a language education through the intensive and regular formation of linguistic abilities. The concept "ability" is analysed and defined in terms of different sciences: psychology, physiology and pedagogy. The linguistic abilities are classified as special abilities. It distinguishes them from general abilities and determines their composition. The structure of these abilities includes primarily components - memory, perception, intellection and a number of secondary qualities which are discussed in the article. Creativity is regarded as a valuable addition to any special abilities and its formation in language study is ensured by using a problem-solving method. Special attention in the article is paid to the issues of motivation and interest which are presented as the significant factors accelerating the formation of linguistic abilities. For determining the level of linguistic abilities, the article substantiates the use of diagnostic tests designed to evaluate the indicators of cognitive processes related to a speech activity. These indicators are ranked and combined into four main groups in accordance with a component composition of linguistic abilities.